Impact-induced porosity and micro-fracturing at the Chicxulub impact structure - Rae,ASP; Collins,G; Morgan,J; Salge,T; Christeson,GL; Leung,J; Lofi,J; Gulick,SPS; Poelchau,M; Riller,U; Gebhardt,C; Grieve,RA; et al. (Journal of Geophysical Research: Planets, 2019)
Porosity and its distribution in impact craters has an important effect on the petrophysical properties of impactites: seismic wave-speeds and reflectivity, rock permeability, strength, and density. These properties are important for the identification of potential craters and the understanding of the process and consequences of cratering. The Chicxulub impact structure, recently drilled by the joint International Ocean Discovery Program and International Continental scientific Drilling Program Expedition 364, provides a unique opportunity to compare direct observations of impactites with geophysical observations and models. Here, we combine small scale petrographic and petrophysical measurements with larger scale geophysical measurements and numerical simulations of the Chicxulub impact structure. Our aim is to assess the cause of unusually high porosities within the Chicxulub peak ring and the capability of numerical impact simulations to predict the gravity signature and the distribution and texture of porosity within craters. We show that high porosities within the Chicxulub peak ring are primarily caused by shock-induced micro-fracturing. These fractures have preferred orientations, which can be predicted by considering the orientations of principal stresses during shock, and subsequent deformation during peak-ring formation. Our results demonstrate that numerical impact simulations, implementing the Dynamic Collapse Model of peak-ring formation, can accurately predict the distribution and orientation of impact-induced micro-fractures in large craters which plays an important role in the geophysical signature of impact structures.